Initial Study and Concept on Analysis of Acute Exposure to Stroboscope Light as a Trigger for Desired Brain Activity Frequency - Natalia BROWARSKA; Jarosław ZYGARLICKI; Mariusz PELC; Michał NIEMCZYNOWICZ; Radek MARTINEK; Edward Jacek GORZELAŃCZYK; Małgorzata ZYGARLICKA; Aleksandra KAWALA-STERNIUK (Communications of International Proceedings, 2021)
The main aim of this work was to present the concept of a study regarding evaluation of a patient's emotional state as a response to visual stimulus, which was in this case - an acute light exposure. The study presented in this work is of preliminary character, however, the authors of this paper are currently working on an appropriate methodology development in order to evaluate the influence of the subjects' alertness level as a response to the exposure on stroboscope light, which shall confirm the previous studies, which states that the frequency of light could elicit the alertness level during the day. It was also important to investigate the correctness of control in a complex measuring system (effective and convenient), and work comfort of the study participants. The obtained (initial) results were very interesting and promising, so further investigation is being planned.
Keywords: Exposure to Light; Brain-Computer Interfaces; Emotiv EPOC Flex; Visual Stimuli.